2022
DOI: 10.1016/j.jinf.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 case-clusters and transmission chains in the communities in Japan

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…There were more transmissions to the elderly from younger age groups as well as elderly-to-elderly transmission in the later phases of each wave. This is consistent with a previous study that reported community cluster outbreaks among the elderly in Japan (Furuse et al, 2021). Since the most severe cases occur in the elderly (Driscoll et al, 2021), interventions focusing on preventing infection in older age groups are essential to minimize the impact of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…There were more transmissions to the elderly from younger age groups as well as elderly-to-elderly transmission in the later phases of each wave. This is consistent with a previous study that reported community cluster outbreaks among the elderly in Japan (Furuse et al, 2021). Since the most severe cases occur in the elderly (Driscoll et al, 2021), interventions focusing on preventing infection in older age groups are essential to minimize the impact of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we were unable to fully assess the heterogeneity of transmission dynamics in specific regions associated with alternative indicators of each NPI because the present study covers the whole of Japan rather than each prefecture. Indeed, the epidemiological effects of NPIs on the transmission dynamics of seasonal influenza may have different probability distributions, as it is necessary to consider the increase in local clusters of COVID-19 in remote prefectures of Japan [ 76 , 77 , 78 , 79 ]. Additionally, compared to severe measures, such as city closures (i.e., lockdown), implemented in other countries, the legal enforcement of the state of emergency declaration in Japan is moderate, and the government relies on people’s voluntary action and the resulting peer pressure to reduce contact at the community level [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the first and second waves, retrospective contact-tracing investigations revealed the source patients and clusters of more than 60% of confirmed cases. After a certain period, especially with the rapid growth of daily cases, the outbreaks in hospitals, healthcare facilities, and schools, posed significant challenges to large-scale case investigation and contract tracing [ 39 ] with inadequate human resources. The number of reported cases without an identified epidemiological link and unrecognized community transmission chains increased [ 40 ].…”
Section: Discussionmentioning
confidence: 99%